Upaya Peningkatan Hasil Belajar Peserta Didik Kelas IV Mata Pelajaran Matematika Bangun Datar Dengan Pemanfaatan Media Interaktif Polypad - Novitasari, Novitasari; Charisma, Dila; Ameliawati, Ameliawati (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
Learning outcomes refer to changes in student achievement after receiving a learning treatment. One effort that can be made is to use Polypad media. This study is a classroom action research that aims to determine the level of change in learning outcomes of class IV C students in mathematics subjects on flat shapes. This PTK research uses the Kemmis & MC Taggart model with four stages, namely planning, action, observation and reflection. This research was conducted in two cycles and each cycle was conducted with two meetings. The subjects of this study were 20 class IV at Megu Gede state Elemenary School . Before the research was conducted, the learning outcomes of students were in the low category with an average score of 45 with a percentage of completion of 15%. After the research was conducted, the cycle I research increased to an average score of 65 with a percentage of completion of 45% and increased again in cycle II to an average score of 85 with a percentage of completion of 85%. The use of polypad media can have a positive impact on the learning outcomes of class IV C students on flat shapes.